2018
DOI: 10.4012/dmj.2017-422
|View full text |Cite
|
Sign up to set email alerts
|

Novel self-etch adhesive with antibacterial and protein-repellent functions to prevent enamel demineralization

Abstract: Enamel demineralization is the most undesired side-effect of fixed orthodontic treatments. This study were to develop a novel adhesive that is self-etching instead of using the traditional etching method, and to form a sealant on the enamel to prevent demineralization. 2-methacryloyloxyethyl phosphorylcholine (MPC) and quaternary ammonium dimethylaminohexadecyl methacrylate (DMAHDM) were mixed into a self-etch adhesive (Adper Easy One, 3M, St. Paul, MN, USA; referred to as AEO). Enamel shear bond strength (SBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Reynolds et al [66] suggested that the appropriate shear bonding strength for orthodontic cements was approximately 8 to 9 MPa, which was high enough to prevent the brackets from falling off the surface of the teeth, while avoiding enamel damage during the debonding process at the completion of the orthodontic treatment. The results of Wang et al [63] showed that the enamel shear bond strength of the self-etch group containing MPC and DMAHDM was 9-10 MPa, which is clinically acceptable. Their research suggested that adding MPC and DMAHDM into the self-etch adhesive exhibited excellent antibacterial and proteinrepellent effect without compromising the bond strength of the brackets.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Reynolds et al [66] suggested that the appropriate shear bonding strength for orthodontic cements was approximately 8 to 9 MPa, which was high enough to prevent the brackets from falling off the surface of the teeth, while avoiding enamel damage during the debonding process at the completion of the orthodontic treatment. The results of Wang et al [63] showed that the enamel shear bond strength of the self-etch group containing MPC and DMAHDM was 9-10 MPa, which is clinically acceptable. Their research suggested that adding MPC and DMAHDM into the self-etch adhesive exhibited excellent antibacterial and proteinrepellent effect without compromising the bond strength of the brackets.…”
mentioning
confidence: 97%
“…Adding either 5% DMAHDM or 7.5% MPC alone into AEO reduced the metabolic activity to nearly 17% and 33% of that of AEO control, respectively. More dramatically, biofilms on the adhesive containing both 7.5% MPC and 5% DMAHDM together had the lowest metabolic activity, which was only 5% of that of AEO control (Figure 6(b)) [63].…”
mentioning
confidence: 98%
See 3 more Smart Citations